Glauben or Wissen? Kant's deceptively simple rejection of atheism - Muñoz Velasco, Julia (Con-Textos Kantianos. International Journal of Philosophy, 2024)
In the “Preface to the second edition” of the Critique of Pure Reason, Kant claims that: “Thus I had to deny knowledge in order to make room for faith.” (Bxxx) In this essay, I will take as a departing point this famous quote to show why Kant rejects any metaphysical conception of atheism, while defending that atheism is a psychological matter, more than a metaphysical one. I will also argue that his conception of a psychological-practical theism entails several problems for Kant’s philosophical system.